The Role of a Smartphone Application in Monitoring the Risk of Hearing Loss Associated with Personal Listening Devices in Young Adults - Deniz Tuz; Selin Sariçamlik; Ceren Bodur; Gülce Kirazli; Pelin Piştav Akmeşe (Noise and Health)
Background Exposure to loud music has been reported to affect high-frequency hearing thresholds in adults. This study aimed to use a mobile application to assess the risk of hearing loss associated with personal listening devices (PLDs) in young adults. Methods A cross-sectional study was conducted on 99 healthy iPhone Operating System (iOS) smartphone users aged 17 to 31 years. Based on their weekly, monthly, 6-month, and annual listening data from the “Health” application, participants were classified into at-risk or non-risk groups. Six individuals in the at-risk group underwent audiological assessments. The Speech, Spatial, and Qualities of Hearing Scale (SSQ) was given to all participants. SSQ scores were compared between groups using the Mann–Whitney U test. The correlation between average PLD sound levels and SSQ scores was analyzed using the Spearman’s test. Results The weekly, monthly, 6-month, and annual listening data showed that 16, 14, 12, and 12 participants were at risk, respectively. All six participants who underwent audiological assessment exhibited normal hearing thresholds. However, a pattern of decline at high frequencies was noted. A significant difference was found between the groups in terms of overall SSQ score (z = −2.74, P = 0.00), speech perception score (z = −3.25, P = 0.00), and hearing quality score (z = −2.01, P = 0.04) based on the 6-month and annual listening data. A weak positive correlation was found between the SSQ scores across all subscales and monthly sound-level data. Exposure duration was negatively correlated with speech perception (r = −0.32, P < 0.05), spatial perception (r = −0.26, P < 0.05), and overall score (r = −0.29, P < 0.05) in weekly data, as well as with hearing quality (r = −0.21; P < 0.05) and overall score (r = −0.21, P < 0.05) in annual data. Conclusions The immediate effects of loud music exposure were absent; however, prolonged exposure resulted in reduced speech perception and hearing-quality levels. Data from the iOS “Health” application indicated that some individuals were at risk of hearing loss, suggesting the need to modify their listening habits to prevent long-term decline in hearing function.